THE ROLE OF TRANSGENDER IN ECONOMY DEVELOPMENT IN MOJOKERTO: A DESCRIPTIVE RESEARCH - Budianto, Lestari; Maknuun, Lu’lu’il; Wahyuni, Firdita; Efendi, Mansur; Ramadhani, Nurcipah; Anisa Nur Faujiah, Siti (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
This descriptive research explores the economic roles and challenges of transgender individuals in Mojokerto, Indonesia, focusing on their experiences of discrimination, economic survival strategies, and community support. Employing a qualitative approach, semi-structured interviews, focus group discussions, and participant observations were conducted with 30 transgender individuals. Findings reveal pervasive discrimination in employment, education, and healthcare, leading many to pursue informal sector work. Despite barriers, transgender individuals demonstrate resilience through entrepreneurship and community networks, contributing to local economic activities. Cultural and religious contexts influence their experiences, sometimes providing unexpected support. Limitations include sample size and potential biases in self-reported data. Recommendations include policy reforms for anti-discrimination laws, inclusive education, healthcare access, and community-based economic initiatives. This study contributes nuanced insights into transgender economic experiences in Mojokerto, advocating for inclusive policies and future research to enhance understanding and support for transgender communities globally.